2012
DOI: 10.1007/s11746-012-2188-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Fatty Acid Composition of the Oil From Sunflower Genotypes Grown in Tropical Regions

Abstract: The influence of temperature on the fatty acid composition of the oils from conventional and high oleic sunflower genotypes grown in tropical regions was evaluated under various environmental conditions in Brazil (from 0° S to 23° S). The amounts of the oleic, linoleic, palmitic and stearic fatty acids from the sunflower oil were determined using gas chromatography (GC). The environment exhibited little influence on the amounts of oleic and linoleic fatty acids in high oleic genotypes of sunflower. In conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
36
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 14 publications
11
36
3
2
Order By: Relevance
“…Genetic factors, abiotic factors such as environmental factors and soil conditions, and their interaction are known to affect the fatty acid composition of plant seed oils [23][24][25][26][27]. In this research, S. mukorossi seed oil-related variables including 100-seed weight, 100-kernel weight, and 100-oil weight were significantly negatively correlated with annual maximum temperature and annual precipitation.…”
Section: Discussionmentioning
confidence: 69%
“…Genetic factors, abiotic factors such as environmental factors and soil conditions, and their interaction are known to affect the fatty acid composition of plant seed oils [23][24][25][26][27]. In this research, S. mukorossi seed oil-related variables including 100-seed weight, 100-kernel weight, and 100-oil weight were significantly negatively correlated with annual maximum temperature and annual precipitation.…”
Section: Discussionmentioning
confidence: 69%
“…Oleic acid content varied, in average (Table 2), from 21.36 to 46.52% and inversely linoleic acid content ranged from 66.47 to 43.53% from colder to warmer environments. HO genotype oils, in turn, showed less (Flagella et al 2002, Izquierdo and Aguirrezábal 2008, Grunvald et al 2013, Van Der Merwe et al 2013). This effect has been attributed to the activity of the oleate desaturase, limited to the early stage of the embryo development (Garcés and Mancha 1991) and also that its transcript is not accumulated during grain filling (Lagravère et al 2004).…”
Section: Resultsmentioning
confidence: 94%
“…Levels of oleic and linoleic acids in sunflower oil have been shown to vary according to temperature after flowering and variation in the oleic acid content to be inversely proportional to variation in the linoleic content (Ungaro et al 1997, Qadir et al 2006, Roche et al 2006, Izquierdo and Aguirrezábal 2008, Turhan et al 2010, Grunvald et al 2013, Van Der Merwe et al 2013, Piao et al 2014. All the authors found the highest oleic acid content when crops were cultivated in warmer environments with higher temperature during seed development, and conversely, linoleic acid content increased when the crop developed under colder environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research topics include the analysis of the operation of national sunflower agri-food chains [15], the description of sunflower production in Brazil [11], a life-cycle assessment of the soybean-sunflower cropping system in MT [14], the analysis of sunflower genotypes' performance at different sowing dates in MT [20], the identification of nematode-resistant sunflower genotypes adapted to the tropical region of Brazil [13], the evaluation of agronomic characteristics of sunflower genotypes cultivated over different regions of the country [21][22][23][24], the analysis of technical characteristics of sunflower oils originated from several genotypes [25,26], and the investigation of the relationship between sunflower productivity and soil´s chemical properties in MT [27]. Nevertheless, to date, no investigation has been conducted to understand the underlying reasons for the rapid development of sunflower sector in MT.…”
Section: Introductionmentioning
confidence: 99%